2020
DOI: 10.21203/rs.2.23102/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Features Of Ocular Myasthenia Gravis In Adult Patients: Diplopia and Ophthalmoplegia

Abstract: Background: The diagnosis of ocular myasthenia gravis (OMG) in adult patients remained challenged and the characteristics of diplopia and ophthalmoplegia in OMG is unclear. Methods: Retrospective case series study of medical records of 40 adult patients diagnosed with OMG at The First Affiliated Hospital of Jinan University from June, 2016 to December, 2019, was performed to analyze the clinical features, diagnostic tests and preferential affected extraocular muscles of OMG. Results: 40 adult patients with OMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
2
Order By: Relevance
“…Die Prävalenz der Myasthenia gravis nimmt zu, wobei die weltweite Prävalenz derzeit auf 20 Personen pro 100 000 Einwohner geschätzt wird [72]. In einer Studie wurde festgestellt, dass bei 82% der untersuchten Patienten eine Augenschwäche das erste Symptom war [73].…”
Section: Autoimmunerkrankungen Und Ihre Auswirkungen Auf Das Augeunclassified
See 1 more Smart Citation
“…Die Prävalenz der Myasthenia gravis nimmt zu, wobei die weltweite Prävalenz derzeit auf 20 Personen pro 100 000 Einwohner geschätzt wird [72]. In einer Studie wurde festgestellt, dass bei 82% der untersuchten Patienten eine Augenschwäche das erste Symptom war [73].…”
Section: Autoimmunerkrankungen Und Ihre Auswirkungen Auf Das Augeunclassified
“…In einer Kohortenstudie von Tang et al wiesen knapp 70% eine Diplopie und 25% eine Ptosis bei der ersten Untersuchung auf. Bei allen 40 Patienten war der seitliche Rektusmuskel betroffen, was zu einer Einschränkung der Augenbewegung führte [73].…”
Section: Autoimmunerkrankungen Und Ihre Auswirkungen Auf Das Augeunclassified
“…The prevalence of myasthenia gravis is increasing, with global prevalence currently estimated to be 20 people per 100,000 population ( 72 ). Notably, one study found an ocular weakness to be the initial symptom in 82% of patients studied ( 73 ).…”
Section: Autoimmune Disorders and Their Ocular Effectsmentioning
confidence: 99%
“…In a cohort study by Tang et al., just under 70% and 25% showed diplopia and ptosis respectively on first evaluation. Of all 40 patients, the lateral rectus muscle was affected, leading to restriction of eye movement ( 73 ).…”
Section: Autoimmune Disorders and Their Ocular Effectsmentioning
confidence: 99%